Desenvolvimento de monolitos baseados em sílica para captura de CO2 - Andressa Aparecida Alves (2018)
With the advent of the Industrial Revolution, there was an exponential growth of population and also the economy, culminating in a considerable increase in the use of fossil fuels, since they are the main sources for power generation. Due to these events, it was noted an increase in the emission of polluting gases. As a result of the high concentration of carbon dioxide (CO2) in the atmosphere, there was an intensication of the greenhouse effect, which is the main responsible for global warming. Because of the great concern with the environmental problems arising from high levels of CO2, several investigations about CO2 capture and storage techniques, are being carried out. A process that has been shown to be quite feasible is the adsorption, since it presents several advantages, such as better separation efciency and easy regeneration. The synthesis of mesoporous materials in macroscopic scale, as for example, the monoliths, has been of great interest in view of the wide range of applications that this material holds. Thus, this work consists of the production of silica monoliths for the purpose of they being used in the CO2 adsorption process. Three silica monoliths were synthesized, all prepared by the sol-gel method, using the tetraethylorthosilicate (TEOS) precursor as the silica source and the following surfactants: cetyltrimethylammonium bromide (CTAB) and Pluronic F127. The materials which presented textural and structural properties suitable for applications adsorbents were prepared again under the same reaction conditions with addition of Al, Ti and Zr, the metal content being varied. In the next step, the samples were functionalized with pentaethylenehexamine (PEHA) and with diethanolamine (DEA) by the wet impregnation method. The materials were characterized by the following techniques: XRD, BET, FTIR, SEM and TG/DTG. The analysis indicated that the materials synthesized with heteroatoms incorporation presented a disordered pore structure and high surface area (about1440m2/gforsampleTi/M3). In addition, they still showe da signicant increase in adsorption of CO2 relative to their parent samples, a fact that is not much explored in the literature. The CO2 adsorption performance tests were carried out at 30 C and atmospheric pressure. All functionalized materials demonstrated improved CO2 adsorption capacity relative to their starting samples. The highest adsorption capacity was 111.3 mg/g for the Ti/M2-P, thus, this adsorbent proved to be a promising candidate for the capture of CO2.